Roles of bacterial extracellular vesicles in systemic diseases - Wang, Yanzhen; Luo, Xinghong; Xiang, Xiaozhen; Hao, Chunbo; Ma, Dandan (Frontiers in Microbiology, 2023)
Accumulating evidence suggests that in various systems, not all bidirectional microbiota-host interactions involve direct cell contact. Bacterial extracellular vesicles (BEVs) may be key participants in this interkingdom crosstalk. BEVs mediate microbiota functions by delivering effector molecules that modulate host signaling pathways, thereby facilitating host-microbe interactions. BEV production during infections by both pathogens and probiotics has been observed in various host tissues. Therefore, these vesicles released by microbiota may have the ability to drive or inhibit disease pathogenesis in different systems within the host. Here, we review the current knowledge of BEVs and particularly emphasize their interactions with the host and the pathogenesis of systemic diseases.